Imperial Physique - Phrydas, JH (punctum books, 2019)
"In 2008, JH Phrydas wrote a story about how bodies talk without words. He wanted the story to not just describe the silent ritual of nonverbal communication but to perform it. The interaction would be visceral - the exchange melancholic, yet full of lust. He wanted words to retain the unsayable: the subtle movements of a body in heat. In the years since, Phrydas kept rewriting this story, using different techniques, different syntaxes and forms, in hopes that he would find a successful method of gestural writing. Imperial Physique is a collection of these attempts. They explore the way our bodies hover between animal and human, civil and wild. The bleakness - and underlying verve - of imagining Western empires in decline serve as a backdrop for a lone figure searching city streets, decaying architecture, and sand dunes for some type of physical connection. What arises is the loss of - and longing for - touch at the edges of imperialism, historical violence, and personal shame."